A 5‐GHz highly linear floating‐body CMOS LNA with switched gain control. Issue 3 (March 2017) - Lee, Muyeon; Kwon, Ickjin
ABSTRACT: A 5‐GHz highly linear floating‐body CMOS low‐noise amplifier (LNA) with switched gain control is presented. The proposed LNA achieves very low noise in gain mode and high linearity and very low power consumption in bypass mode. In the gain mode, the LNA consumes 19.5 mW of power and achieves a noise figure of 1.15 dB, a gain of 13.8 dB, and an input IP3 of 3 dBm at 5 GHz. In the bypass mode, the LNA consumes only 1 μW and achieves a gain of −4.3 dB and an input IP3 of 7 dBm at 5 GHz. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:593–596, 2017